The impact of the use of electronic concept maps in understanding grammatical rules - Abdou, Haiam Nasreldin (Journal of Educational and Psychological Sciences, 2020)
The study aimed at uncovering the effect of the use of electronic concept maps in understanding grammatical rules of students of Qassim colleges in Saudi Arabia. For this purpose, the researcher prepared the grammatical rules using the electronic concept maps and used the descriptive method. (30 female students) and experimental group (30 female students), and applied the tribal test to both groups, and after reassurance in the same way, experimental treatment was provided using grammatical rules designed with e-concept maps with experimental group students, and grammatical rules were introduced in the usual way for control group students. E-concept maps explain grammar rules to students in the control group. The study recommends the use of electronic concept maps to explain grammatical rules.
Keywords: Electronic Concept Maps; Grammar